Collaborative mathematics learning management: Critical thinking skills in problem solving - Sutama Sutama; Djalal Fuadi; Sabar Narimo; Siti Hadiyati Nur Hafida; Meggy Novitasari; Sofyan Anif; Harun Joko Prayitno; Sunanih Sunanih; Mazlini Adnan (International Journal of Evaluation and Research in Education (IJERE), 2022)
This qualitative-ethnography study described the critical thinking skill based on indicators of interpretation, analysis, evaluation, and inference in solving mathematical problem. The subjects of the study were the headmaster, math teachers, and ninth grade students of a public junior high school in academic year of 2020/2021. The data were collected through observation, field notes, interview, and documentation. Triangulation of sources and technique were used to ensure the data validation in this research. Data analysis technique was done inductively with continuous process along with the data collection. The results of the study showed high initial skills in mathematics become the basic need for the students in developing critical thinking skills based on indicators of interpretation. The improvement of critical thinking based on the indicator of interpretation is accustomed through problem-based learning. Critical thinking process based on the indicator of analysis is cultivated through collaborative learning. In this indicator, the students need special attention from the teacher. There is always the possibility for every student from each level to face difficulties in solving some problems without collaborating with others. The teachers can make more effort to optimize the students’ basic holistic skills in line with their knowledge and experience in order to improve students’ critical thinking skills based on the indicator of inference. In this indicator, teachers should guide the students to improve their critical thinking skills.